Development of Media Puzzle Using Game Based Learning Approach to Improve Learning Outcomes Student Mathematics in Elementary School - Riskyka; Lubis, Renni Ramadhani; Yusnita, Novi Cynthia (Journal of Elementary School Education, 2023)
This study aims to develop media puzzles with a game based learning approach to improve students' mathematics learning outcomes in elementary schools. This research is a research and development (RnD) research, using a 4-D development model, including: 1) define, 2) design, 3) develop and 4) disseminate. The subjects of this study were 25 grade IV students consisting of 9 male students and 16 female students. The research object is puzzle media with a game based learning approach. Data collection techniques are observation, questionnaires, and tests. Based on the validation results of the puzzle media with the game based learning approach, it shows that: (1) the level of validity of the puzzle media with the game based learning approach gets an average score from material and media experts of 4.29 and 4, 17 with the categories "very valid" and "valid", (2) the level of effectiveness was tested through tests with the result that 80% of students could be said to be complete. This means that the puzzle media with a game-based learning approach is very effective in improving student learning outcomes, (3) the practical level of puzzle media with a game-based learning approach through teacher and student response questionnaires with an average score of 4.09 and 3.86 in the "practical" category. Based on these results, it can be concluded that puzzle media with a game based learning approach is feasible and effective for use in elementary schools. (3) the level of practicality of puzzle media with a game based learning approach through a teacher and student response questionnaire with an average score of 4.09 and 3.86 in the "practical" category. Based on these results, it can be concluded that puzzle media with a game based learning approach is feasible and effective for use in elementary schools. (3) the level of practicality of puzzle media with a game based learning approach through a teacher and student response questionnaire with an average score of 4.09 and 3.86 in the "practical" category. Based on these results, it can be concluded that puzzle media with a game based learning approach is feasible and effective for use in elementary schools.